SHORT DURATION HEAD-UP TILT TEST: A COMPARISON WITH CONVENTIONAL LONG PROTOCOL IN PATIENTS OF ORTHOSTATIC INTOLERANCE - Khan, Humaira Fayyaz; Hameed, Muhammad Amjad; Khan, Umar Ali (Journal of Ayub Medical College Abbottabad, 2010)
Background: Orthostatic intolerance is development of symptoms during upright standing relieved by recumbency. An individual's predisposition to orthostatic intolerance (development of symptoms during upright posture) can be identified by Head-up Tilt Test (HUT). The aim of the present study was to compare the diagnostic yield (Percentage of patients tested positive) of short duration with conventional HUT. Methods: The study was conducted in Islamic International Medical College, Rawalpindi in collaboration with Armed Forces Institute of Cardiology/National Institute of Heart Diseases. A total number of 100 patients with orthostatic intolerance were studied. The conventional and short duration HUT protocols were compared. Conventional protocol had a passive tilt phase of 30 minutes and drug provocation phase of 20 minutes while the short duration protocol had both phases of 15 minutes, thereby reducing the test duration by 20 minutes. All patients underwent short duration HUT and patients with positive test were considered positive for conventional HUT as well. Patients having negative short duration HUT underwent conventional HUT after one week. Comparison was done using Chi-square statistics and p<0.05 was considered significant. Results: Diagnostic yield of short duration and conventional HUT was 53% and 63% respectively with no statistically significant difference between the two protocols (p=0.15). Conclusions: Head-up tilt test (HUT) is an effective investigative tool for orthostatic intolerance with satisfactory diagnostic yield. Short duration HUT may be substituted for conventional HUT to save time and to accommodate more patients. Keywords: Orthostatic intolerance, Head-up tilt test, Nitroglycerine